2022
DOI: 10.1017/s1366728922000803
|View full text |Cite
|
Sign up to set email alerts
|

Graded bilingual effects on attentional network function in Chinese high school students

Abstract: Effective communication in multilingual environments requires bilinguals to constantly monitor linguistic cues. It is hypothesized that the constant need to monitor may result in improved attention. However, previous investigations have reported mixed, often null results, with positive findings attributed to non-linguistic variables. To address these issues, we investigated whether higher levels of bilingualism were associated with improved attentional function in a sample of culturally and socioeconomically h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 93 publications
1
8
0
Order By: Relevance
“…Finally, separable dimensions of FL experience, often interacting with each other, impacted on ratings of permissibility and, in the personal version of the Trolley dilemma only, ratings of distress. This work adds to a growing literature investigating graded effects of separable dimensions of language experience on previously reported psycholinguistic phenomena (Privitera et al, 2022a(Privitera et al, , 2022b. We did not observe an MFLE consistently across all dilemmas, replicating the null and mixed findings of some previous studies (Čavar & Tytus, 2018;Costa et al, 2014;Del Maschio et al, 2022b;Wong & Ng, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Finally, separable dimensions of FL experience, often interacting with each other, impacted on ratings of permissibility and, in the personal version of the Trolley dilemma only, ratings of distress. This work adds to a growing literature investigating graded effects of separable dimensions of language experience on previously reported psycholinguistic phenomena (Privitera et al, 2022a(Privitera et al, , 2022b. We did not observe an MFLE consistently across all dilemmas, replicating the null and mixed findings of some previous studies (Čavar & Tytus, 2018;Costa et al, 2014;Del Maschio et al, 2022b;Wong & Ng, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…The cognitive benefits of bilingualism have been supported by studies (e.g., Hilchey and Klein, 2011 ; Bialystok and Craik, 2022 ; Xie et al, 2023 ). In addition, studies have supported a positive relationship between M–E bilinguals' L2 proficiency and inhibitory control (Privitera et al, 2022 ), and between L2 proficiency and attentional control (Privitera et al, 2023 ). Li and Zhang's ( 2019 ) study showed that M–E bilinguals' retrieval of temporal concepts was closely related to the cognitive load of the task.…”
Section: Discussionmentioning
confidence: 99%
“…As the participants in our study were homogeneous in terms of demographics and education, dimensions of language experience other than L1 and L2 proficiencies, such as AoA, L2 dominance, L1–L2 dominance ratio, and L2 immersion, were not included. Previous studies have shown that different dimensions of language experience would have different influences on bilinguals' cognitive processing (Gullifer et al, 2021 ; Privitera et al, 2023 ), so further studies may be conducted to examine the effects of multidimensional language experience.…”
Section: Limitationmentioning
confidence: 99%
See 1 more Smart Citation
“…In combination with the collection of detailed data on language experience (De Bruin, 2019; Gullifer et al, 2021; Li et al, 2020; Luk & Bialystok, 2013; Marian et al, 2007) and other nonlinguistic variables (e.g., Bak, 2016; Naeem et al, 2018; Samuel et al, 2018; Van den Noort et al, 2019; Ware et al, 2020), mixed-effects analyses provides an opportunity for meaningful individual differences in bilingual and nonlinguistic experience to be tested in investigation of bilingual effects on executive function before rejecting the hypothesis based on an incomplete test of the hypothesis. One recent investigation found that models that do not consider individual differences in baseline task performance result in the identification of significant bilingual effects that become nonsignificant when these differences are accounted for using mixed-effects models (Privitera et al, in review). Although only four studies using mixed-effects analysis methods were identified during the search for the present review (Kuipers & Westphal, 2021; Oschwald et al, 2018; Samuel et al, 2018; Von Bastian et al, 2016), their alignment with the paradigm shift in experimental methods in psycholinguistics supports these methods are appropriate for use in the investigation of bilingual effects on attention and inhibition.…”
Section: Discussionmentioning
confidence: 99%